A new class of natural anthelmintics targeting lipid metabolism - Hala Zahreddine Fahs; Fathima S. Refai; Suma Gopinadhan; Yasmine Moussa; Hin Hark Gan; Yamanappa Hunashal; Gennaro Battaglia; Patricia G. Cipriani; Claire Ciancia; Nabil Rahiman; Stephan Kremb; Xin Xie; et al. (Nature Communications)
Abstract Parasitic helminths are a major global health threat, infecting nearly one-fifth of the human population and causing significant losses in livestock and crops. Resistance to the few anthelmintic drugs is increasing. Here, we report a set of avocado fatty alcohols/acetates (AFAs) that exhibit nematocidal activity against four veterinary parasitic nematode species: Brugia pahangi, Teladorsagia circumcincta and Heligmosomoides polygyrus, as well as a multidrug resistant strain (UGA) of Haemonchus contortus. AFA shows significant efficacy in H. polygyrus infected mice. In C. elegans, AFA exposure affects all developmental stages, causing paralysis, impaired mitochondrial respiration, increased reactive oxygen species production and mitochondrial damage. In embryos, AFAs penetrate the eggshell and induce rapid developmental arrest. Genetic and biochemical tests reveal that AFAs inhibit POD-2, encoding an acetyl CoA carboxylase, the rate-limiting enzyme in lipid biosynthesis. These results uncover a new anthelmintic class affecting lipid metabolism.